CLONING OF GENES ENCODING TRANSMEMBRANE PROTEINS AND PROTEINS RESPONSIBLE FOR AFRICAN SWINE FEVER VIRUS VIRULENCE - Ali Mazloum; N. G. Zinyakov; A. S. Igolkin; N. N. Vlasova (Ветеринария сегодня)
Results of cloning X69R, A179L, E248R, I215L and DP96R genes of ASF virus Krasnodar 07/17 isolate and analysis of their nucleotide sequences are presented. Obtained clones were added to the previously constructed clone library comprising clones of 8 genes of Krasnodar 06/12 isolate. Clones containing X69R, A179L, E248R, I215L and DP96R genes of ASF virus Krasnodar 07/17 isolate will be used for recombinant protein obtaining and testing for their effect on in vitro virus reproduction and their role in the virus infectivity, level of clinical manifestations and virulence. Prokaryotic vector, pJET1.2/ blunt, was used. Thus, the clone library available at the FGBI “ARRIAH” Reference Laboratory for African swine fever was supplemented by pJET1.2-X69R, pJET1.2-A179L, pJET1.2-E248R, pJET1.2-I215L and pJET1.2-DP96R plasmid constructions containing 5 genes of ASF virus Krasnodar 07/17 isolate. Proportion of cloned virus genes was 3.01% of Krasnodar 07/17 isolate genome, hence, total amount of the clone library has reached 7.82%.